What Color is Your C.F.R.? - Dyszlewski, Nicole; M. Ortiz, Raquel (Open textbook library., 2016)
What Color is Your C.F.R.? is a problem-based law workbook with a colorful twist. Conceived and written by law librarians, it uses easy to understand plain language and is a light-hearted but helpful supplement to instruction on basic legal research. The book takes a non-traditional approach to legal research and uses short legal research exercises and coloring.